Malay Royal Institutions according to the Federal Constitution within the context of ethnic relations in Malaysia - Nazri Muslim,; Azizi Umar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Malay Royal Institution has existed for centuries in the social system of the administration of Malay states in Malaysia. In this monarchy system, the sovereign has the absolute power in the state administration. However, during British colonization, the Sultan had to refer to the Resident as advisor except on matters related to Islam and Malay customs. The situation continued until the Malayan Union was introduced in 1946 when the Sultan was only authoritative on the Malay customs and Islam, while the state administration was held by the Governor. When the Malayan Union Constitution was replaced by the Malay Federation in 1948, the Sultan was given the rights to rule the country in accordance with the Constitutional Monarch. This study aims to analyze the perception of undergraduates at public higher education institutions regarding the Malay Royal Institution in the Federal Constitution within the context of ethnic relations in Malaysia. It involved 422 respondents selected from 4 public higher education institutions in Malaysia. The data obtained through surveys was analysed using SPSS program. Descriptive statistics such as frequency was used to describe the background of the respondents and to analyze the students’ perception. The findings show that the acceptance level of the students on the position of Malay Royal Institutions in the constitution is relatively and generally high. Based on the findings, several recommendations are put forward to address issues related to the position of the Malay Royal Institution. This study also contributes to the field of knowledge as the methodology employed was quantitative which was different from previous studies which used qualitative methods.